Peran TPA Al-Hidayah Sindon sebagai Pendukung Pembelajaran Fikih di Madrasah Ibtidaiyah - Fatiha Azizah; Jovita Dwi Kusumastuti; Qodim Ma’shum (PT. Nawa Edukasi Nusantara, 2026)
This study aims to determine the role of TPA Al-Hidayah Sindon in supporting fiqh learning for Madrasah Ibtidaiyah (MI) students. The study is motivated by the importance of non-formal education in strengthening children’s religious understanding, especially in daily worship practices. This research employed a qualitative approach with a descriptive research type. Data collection techniques were carried out through observation, interviews, and documentation involving teachers and students of TPA Al-Hidayah Sindon. The results showed that TPA Al-Hidayah Sindon plays an important role in supporting fiqh learning through Qur’an reading and writing activities, Islamic Religious Education (PAI) materials, worship practices, and Islamic educational games. Learning activities are conducted every Monday, Wednesday, and Friday with approximately 35 students aged 6–12 years. The learning methods applied are practice and habituation, which help students better understand worship procedures such as ablution, prayer, and daily supplications. In addition to improving fiqh understanding, the TPA also contributes to building children’s religious character through discipline, politeness, and religious activities. Therefore, TPA Al-Hidayah Sindon serves as an effective non-formal educational institution in supporting fiqh learning for MI students and strengthening Islamic education within the community.